Design and Construction of A Back Muscle Injury Detection Device based on The Fuzzy Logic Method - Hajri, M Aidil; Rahmadya, Budi (CHIPSET, 2026)
Lifting is a common task. This work typically requires muscle strength, especially the back muscles. However, this work carries a risk of back injury if performed incorrectly or inappropriately. Using a back muscle injury detection system can reduce the risk of back muscle injury. This system uses an EMG sensor to measure the electrical signals generated by muscle activity to gauge the level of muscle activity. This will be used as a reference for determining risk factors for back muscle injury. A buzzer sensor is used to provide information about muscle condition and warn of muscle injury. This system uses fuzzy logic to classify muscle activity levels while assisting the output process on the buzzer. The system successfully detects electrical signals in the back muscles with a range of 10 µ v - 30 µ v.